Kajian Historis Pembentukan Khalifah di Massa Abubakar As-Siddiq - Jufri Yusup; Ansar Tohe (Al-Kindi, 2026)
This study examines the formation of the caliphate during the leadership transition following the death of Prophet Muhammad SAW, with a particular focus on the appointment of Abu Bakr Ash-Shiddiq as the first caliph of Islam. The research aims to analyze the concept of the caliphate, the process of Abu Bakr's appointment through deliberation (shūrā) at Saqifah Bani Sa'idah, and the implications of his leadership for the development of the Islamic political system. This study employs a qualitative library research method using a historical and descriptive-analytical approach. Data were collected from primary sources, including the Qur'an, Hadith, and classical Islamic historical works, as well as secondary sources such as scholarly books and journal articles. The findings reveal that the appointment of Abu Bakr was based on consultation and collective consensus rather than hereditary succession, reflecting the principles of justice, trustworthiness, and public welfare. Furthermore, Abu Bakr's leadership successfully maintained the unity of the Muslim community, suppressed the Ridda movements, enforced zakat obligations, and established the administrative and political foundations of the Khulafaur Rashidin government, demonstrating that effective leadership is rooted in integrity, consultation, and commitment to the common good.